Coral Communities on Marginal High-Latitude Reefs in West Australian Marine Parks - Claire L. Ross (MDPI AG, 2021)
Many temperate reefs are experiencing a shift towards a greater abundance of tropical species in response to marine heatwaves and long-term ocean warming worldwide. Baseline data for coral communities growing in high-latitude reefs is required to better understand ecosystem changes over time. In this study, we explore spatial and temporal trends in the distribution of coral communities from 1999 to 2019 at 118 reef sites within the five marine parks located in the south-west of Western Australia (WA) between 30° to 35° S. Our estimates of coral cover were generally low (<5%), except for a few sites in Jurien Bay Marine Park and Rottnest Island Marine Reserve where coral cover was 10% to 30%. Interannual changes in genera assemblages were detected but were not consistent over time, whereas significant temporal increases in coral cover estimates were found at the lowest latitude site in Jurien Bay. Coral assemblages were primarily distinguished by Turbinaria spp. at Marmion Marine Park and Ngari Capes Marine Park, and Pocillopora spp. and Dipsastraea spp. at Rottnest Island and Jurien Bay. Our findings suggest that conditions in south-west WA are favorable to the ongoing survival of existing genera and there were minimal signs of expansion in coral cover at most study sites. Coral cover and composition on these reefs may, however, change with ongoing ocean warming and increased occurrence of marine heatwaves. This study provides a valuable benchmark for assessing future changes in coral assemblages and highlights the need for targeted hard-coral surveys to quantify subtle changes in high-latitude coral community assemblages.